HUBUNGAN PEMAHAMAN DAN MOTIVASI WANITA USIA SUBUR (WUS) DENGAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) DI DESA SUNGAI TUAN ULU KAB. BANJAR TAHUN 2022 - Raihana Norfitri; Zubaidah Zubaidah; Rusdiana Rusdiana; Susanaria Alkai (Sekolah Tinggi Pariwisata Mataram, 2023)
Cervical cancer can certainly be detected earlier by using the Visual Acetate Inspection (IVA) test. The purpose of the Visual Acetate Inspection (IVA) examination is to reduce morbidity and mortality from disease by early treatment of cases found and to find out abnormalities that occur in the cervix. This study aims to analyze the relationship between understanding and motivation of women of childbearing age with a visual inspection of acetic acid (IVA) in Sungai Tuan Ulu Village, Kab. Banjar. This research method uses a correlation analytic research design with a cross sectional approach. The population in this study were 50 women of childbearing age using a sampling technique, namely total sampling and a sample of 50 respondents. The results showed that women of reproductive age about cervical cancer had sufficient knowledge (58%) and high motivation (80%). The results of Spearman's rho analysis, P value = 0.04 (α = 0.05) means that HA is accepted. The conclusion in this study is that there is a relationship between understanding and motivation of women of childbearing age (WUS) with a visual inspection of acetic acid (IVA). Suggestions are that it is hoped that public knowledge about cervical cancer and visual inspection of acetic acid (IVA) will be increased by expanding health promotion targets through counseling and other methods.